Literary theory and the claims of history : postmodernism, objectivity, multicultural politics - Mohanty, Satya P. (Satya Prakash), 1954- (Cornell University Press, 1997)
Drawing on detailed analyses of reference, interpretation, and the nature value, Satya P. Mohanty defends a "postpositivist realist" conception of objectivity as a legitimate ideal of all inquiry. He outlines a realist theory of social identity and multicultural politics, showing why radical moral universalism and cultural diversity need to be seen a complementary, rather than competing ideals.